1989
DOI: 10.1177/000456328902600406
|View full text |Cite
|
Sign up to set email alerts
|

Glycated Haemoglobin and other Biochemical Parameters in Sudanese Diabetics

Abstract: SUMMARY.Fasting levels of glycated haemoglobin, cholesterol and triglycerides were studied in 44 patients with non-insulin-dependent diabetes mellitus (NIDDM), 31 patients with insulin-dependent diabetes mellitus (IDDM) and 28 healthy Sudanese individuals. Results confirmed previous observations showing correlation of glycated haemoglobin with fasting blood glucose in NIDDM (r=0'634; P Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…These results coincide with those of other authors (Winocour et al, 1989;Peña et al, 1994). Atabani et al (1989) found positive correlations between serum levels of total cholesterol and HbA1c (r ¼ 0.36, P < 0.05). Our study presents a statistically significant correlation of VLDLc with HbA1c (r ¼ 0.42, P ¼ 0.003), together with a positive significant correlation of the different atherogenic indices with HbA1c (LDLc=HDLc, r ¼ 0.42, P ¼ 0.003; (VLDLc þ LDLc)=HDLc, r ¼ 0.42, P ¼ 0.003).…”
Section: Influence Of Metabolic Control Of the Illness On Atherogenicmentioning
confidence: 86%
“…These results coincide with those of other authors (Winocour et al, 1989;Peña et al, 1994). Atabani et al (1989) found positive correlations between serum levels of total cholesterol and HbA1c (r ¼ 0.36, P < 0.05). Our study presents a statistically significant correlation of VLDLc with HbA1c (r ¼ 0.42, P ¼ 0.003), together with a positive significant correlation of the different atherogenic indices with HbA1c (LDLc=HDLc, r ¼ 0.42, P ¼ 0.003; (VLDLc þ LDLc)=HDLc, r ¼ 0.42, P ¼ 0.003).…”
Section: Influence Of Metabolic Control Of the Illness On Atherogenicmentioning
confidence: 86%